2020
DOI: 10.1039/d0en00398k
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter influences transformation products of ferrihydrite exposed to sulfide

Abstract: In the presence of sulfide, organic matter influences iron mineral transformation pathways and kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 83 publications
(206 reference statements)
2
20
0
Order By: Relevance
“…Even in sulfidic mine rock and drainage environments often characterized by very low biodiversity [24], Bao et al [169] found that Fe(III)-and sulfate-reducing bacteria significantly enhanced the conversion of schwertmannite and jarosite, with organic carbon being the major factor limiting the conversion rate. Organic matter is also found to affect the transformation of ferrihydrite to lepidocrocite and goethite [170]. These microorganisms utilize secondary minerals as the terminal electron acceptors via two mechanisms (Figure 5): direct electron transfer by attaching to the mineral surfaces using motility proteins and flagella; indirect electron transfer by producing endogenous electron shuttles and Fe(III) complexing agents, e.g., quinones or siderophores [171].…”
Section: Transformation Of Secondary Minerals Mediated By Microorganismsmentioning
confidence: 99%
“…Even in sulfidic mine rock and drainage environments often characterized by very low biodiversity [24], Bao et al [169] found that Fe(III)-and sulfate-reducing bacteria significantly enhanced the conversion of schwertmannite and jarosite, with organic carbon being the major factor limiting the conversion rate. Organic matter is also found to affect the transformation of ferrihydrite to lepidocrocite and goethite [170]. These microorganisms utilize secondary minerals as the terminal electron acceptors via two mechanisms (Figure 5): direct electron transfer by attaching to the mineral surfaces using motility proteins and flagella; indirect electron transfer by producing endogenous electron shuttles and Fe(III) complexing agents, e.g., quinones or siderophores [171].…”
Section: Transformation Of Secondary Minerals Mediated By Microorganismsmentioning
confidence: 99%
“…21,22 Sulfidation of various iron (oxyhydr)oxides has been widely studied under different environmental conditions. [8][9][10]21,23,24 According to their reactivities toward dissolved sulfide, common iron (oxyhydr)oxides can be broadly divided into two groups: highly reactive minerals with a lower degree of crystal order (like ferrihydrite and lepidocrocite) and less reactive but more ordered ones (such as hematite and goethite). 21 Magnetite has long been regarded as one of the less reactive phases due to its relatively long half-life (tens of days) for sulfidation.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 4 Some of the difficulties are due to the complicated electronic structure of these systems, existence of nonstoichiometric phases, and environment-dependent reactivity. 11 , 12 Several recent computational investigations have focused on the static properties of these systems, including the electronic structure and geometry in the gas phase. 13 16 Other studies utilized nonreactive interatomic potentials and provided important details of their structural properties and the associated bulk phases.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread applications of iron–sulfur clusters, controversy remains regarding their structure and stability in aqueous environments . Some of the difficulties are due to the complicated electronic structure of these systems, existence of nonstoichiometric phases, and environment-dependent reactivity. , Several recent computational investigations have focused on the static properties of these systems, including the electronic structure and geometry in the gas phase. Other studies utilized nonreactive interatomic potentials and provided important details of their structural properties and the associated bulk phases . However, analysis of the dynamic nature of the clusters, or the effects of a surrounding aqueous environment, is scarce and limited to ab initio approaches. , …”
Section: Introductionmentioning
confidence: 99%